Short Comings of Criminal Justice System of Pakistan and its Effects on the Rights of Accused Prisoner Wrongfully Convicted or Imprisoned - QAYUM, Sara; FARID, Sughra; SHEHZAD, Suhail; ZHU, Weidong (Journal of Legal Studies, 2016)
The criminal justice system in Pakistan operates imperfectly, although the aim of the Pakistan‟s Criminal Law system is that no person is being convicted without all the elements but our System is not speedy and fast in disposal of cases then automatically innocent suffers. A failure of the justice system leaves people free but uncompensated. When a case has been decided after a lengthy trial and an individual acquit on merit by the judgment of concerned Court than upon release he did not receive any thing as compensation by the Criminal Justice System of Pakistan because System offers no mechanism for compensation. This article will discuss about wrongfully convicted persons in Pakistan‟s Criminal Justice System and the reasons for their wrongful imprisonment and mechanism for compensation. In the end, conclusions and recommendations will be given on the same.